Recovery of valuable heavy minerals via gravity and magnetic separation operations from Diit Quaternary stream sediments, southern coast of the Red Sea, Egypt. Issue 1 (1st August 2022) - Fawzy, M M; Abu El Ghar, M S; Gaafar, I M; El Shafey, A M; Diab, M; Hussein, A W
Abstract: This research aims to concentrate and recover valuable heavy minerals (VHMs) contained in Diit area, southern coast of the Red Sea, Egypt. In this study, three technological samples were collected representing Lens, Delta and Wadi Diit; mineralogical investigation followed by mineral processing was performed in order to recover VHM content. VHMs such as zircon, ilmenite, rutile, sphene, apatite, garnet, and magnetite have been recorded in associations with lesser amounts of uranothorite, monazite, xenotime, fergusonite, khatyrkite, and gold. Initially, two stage wet gravity concentration processes, rougher and scavenger, were carried out via a shaking table to produce a clean concentrate of VHMs, which was used as feed material for the magnetic separation process. Magnetic separation was performed in order to separate ferromagnetic minerals from paramagnetic minerals as well as diamagnetic minerals to obtain clean concentration of these fractions. Assay and Material balance of the concentration steps proved that the THM content of Diit lens increased to 89.70% with a recovery of 91.68% in a weight of 61.08% out of the original sample. While the percentage of THM content in Wadi and Delta Diit samples increased to 48.68 and 47.67% respectively, with recovery equivalent to 71.67 and 82.06% respectively in a weight of 16.51, 18.7% respectively out of the original sample. Finally, a process flowsheet was created according to the optimum conditions for concentration and separation processes.